Factors Affecting Employee Work Motivation at PT. PLN Persero ULP Teluk Segara Bengkulu - Afrian Renaldy; Neri Susanti; Yanto Effendi (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
This study aims to determine the factors that most affect the work motivation of employees at PT PLN Persero ULP Teluk Segara Bengkulu. The analytical methods used were validity test, reliability test, multiple linear regression, coefficient of determination, F test and t test. Based on the research results show that: Multiple linear regression equation obtained Y = -1.740 + 0.090X1 + 0.201X2 + 0.326X3 + 0.471X4 + e. The desire to live (X1) has a significant effect on the work motivation of state civil servants (Y) at PT. PLN Persero ULP Teluk Segara Bengkulu because the significance value is 0.007 < 0.05. The desire for a position (X2) has a significant effect on the work motivation of state civil servants (Y) at PT. PLN Persero ULP Teluk Segara Bengkulu because the significance value is 0.000 <0.05. The desire for power (X3) has a significant effect on the work motivation of state civil servants (Y) at PT. PLN Persero ULP Teluk Segara Bengkulu because the significance value is 0.009 < 0.05. The desire for recognition (X4) has a significant effect on the work motivation of state civil servants (Y) at PT. PLN Persero ULP Teluk Segara Bengkulu because the significance value is 0.000 < 0.05. The desire to live (X1), the desire variable for a position (X2), the desire for power variable (X3), the desire for recognition variable (X4), simultaneously or together have a significant effect on employee motivation (Y) at PT. PLN Persero ULP Teluk Segara Bengkulu because the significance value is 0.000 < 0.05.